Neurofibromatosis Current Trends and Future Directions - Signorelli, Francesco; Messina, Raffaella (IntechOpen, 2020)
Neurofibromatosis, one of the most common genetic disorders, is a group of three conditions-Neurofibromatosis 1, Neurofibromatosis 2 and Schwannomatosis-that share some clinical features, such as the presence of cranial and spinal nerve sheet tumors. However, they differ in type of genetic disorder, age of clinical onset, manifestations, management and prognosis. Due to multisystem involvement, a multidisciplinary treatment approach that includes research is ideal. This book provides a systematic, comprehensive and updated outline of Neurofibromatosis. It is a useful reference for clinicians, researchers and students.